Central Administration of Galanin Receptor 1 Agonist Boosted Insulin Sensitivity in Adipose Cells of Diabetic Rats - Zhang, Zhenwen (J Diabetes Res, 2016)
Our previous studies testified the beneficial effect of central galanin on insulin sensitivity of type 2 diabetic rats. The aim of the study was further to investigate whether central M617, a galanin receptor 1 agonist, can benefit insulin sensitivity. The effects of intracerebroventricular administration of M617 on insulin sensitivity and insulin signaling were evaluated in adipose tissues of type 2 diabetic rats. The results showed that central injection of M617 significantly increased plasma adiponectin contents, glucose infusion rates in hyperinsulinemic-euglycemic clamp tests, GLUT4 mRNA expression levels, GLUT4 contents in plasma membranes, and total cell membranes of the adipose cells but reduced the plasma C-reactive protein concentration in nondiabetic and diabetic rats. The ratios of GLUT4 contents were higher in plasma membranes to total cell membranes in both nondiabetic and diabetic M617 groups than each control. In addition, the central administration of M617 enhanced the ratios of pAkt/Akt and pAS160/AS160, but not phosphorylative cAMP response element-binding protein (pCREB)/CREB in the adipose cells of nondiabetic and diabetic rats. These results suggest that excitation of central galanin receptor 1 facilitates insulin sensitivity via activation of the Akt/AS160 signaling pathway in the fat cells of type 2 diabetic rats.